Design of communal rainwater harvesting system for residential areas in Metro Manila Brgy. Daang Bakal, Mandaluyong City case study - Asistin, Georgia Mae B.
The main purpose of the study is to provide a design for a communal rainwater harvesting system in an urban residential community in Metro Manila in the case of Brgy. Daang Bakal in Mandaluyong City. It aims to identify the required design parameters and the appropriate methodology to determine the capacity and design of the storage tank, collection, and distribution networks. To lessen water stresses in existing resources, rainwater can be utilized by exploring the technology of harvesting at a larger scale. A communal rainwater harvesting system can be a supplementary water source that can cover the non-potable water demand of the residential area. Twenty year rainfall data from PAG-ASA and the non-potable water demand from a survey done were used to determine the storage size using the Rational Method and the Yield After Spill algorithm. Roof areas were estimated using the average residential floor area from a survey. Necessary road measurements and elevations were obtained from a geographic information system such as Google Earth. Hydraulic design computations were done and verified using the EPANET software. The software was used to simulate the hydraulic behavior within the pipe networks during collection and distribution. The total cost of the main CRWH system components is also determined along with the amount of water saved in terms of volume and cost using the system. A booklet containing the framework for the design of the CRWH system adapted to the Philippine urban setting was also produced.